Efektivitas Metode Gallery Walk dalam Meningkatkan Hasil Belajar Fiqih Kelas V SD/MI - Diah Hany Hany Retnosari; Musaadatul Fithriyah (Universitas Islam Lamongan, 2020)
Abstract: This research discusses the effectiveness of the Gallery Walk learning method in improving the learning outcomes of Hajj fiqh. ThisIresearchIis motivatedUbyItheIlowEstudentIlearningIoutcomes of class V. The problem formulation inIthisIstudyIisIHowIis theIapplicationIofIthe Gallery Walk method in the subject of Hajj fiqh in MI Fathul Huda class? In class V MI Fathul Huda ?. This study uses quantitative research, using a Noniquivalent Control_Group Desig_Experiment research design. The sample in this research is VB and VA grade students, amounting to 40 students. Data collection techniques and instruments: (1) Interview, (2) Test of learning outcomes, (3) Documentation. To find out student learningIoutcomesIusingIpre-test and post-test questions. The instrument, before being used in the study, was first validated and reliably. After that, the hypothesis test uses the t-test is the Independent Sample T-Test. TheIresultsIofIthisIstudyAindicateI